Temsil-Taklit İlişkisi Açısından Tasvirin Teorik Zemini -İbnü’l-Arabî’nin Eserleri Esasında - Gemuhluoğlu, Zeynep (FSM Vakıf Üniversitesi, 2019)
Tasvir meselesinin kökenindeki sûret ve temsil konusu, başlangıcından günümüze kadar bütün bir felsefe tarihinin de en temel problemidir ve bu yüzden söz konusu tartışmalar da sadece sanata özgü değildir. Tasvirin temsil ve taklit kavramları ile ilişkisi, epistemoloji-ontoloji merkezinde felsefenin, isim-sıfat tartışmaları açısından teolojinin ve elbette ahlâkın zeminini belirler. Bu makalede tasvir meselesinin felsefe açısından varlık ve oluş, teolojik açıdan da yaratma ve kurtuluş kavramlarıyla ilgisi tartışılarak temsil ve taklidin teorik zemini belirlenmeye çalışılmaktadır. Makale ayrıca meselenin İbnü’l-Arabî metinleriyle nasıl yorumlanabileceğini göstermeyi hedeflemektedir.

The problem of representation and mimesis which is at the roots of the issue of depiction (taswir) is from the beginning until now the most basic problem within the whole body of philosophy and, therefore, arguments in question are not limited to art only. The relation between depiction (taswir) and the concepts of representation and mimesis define the foundations of philosophy in terms of epistemology-ontology, theology with regard to ‘name-designation’ discussions, and, with no doubt, morality. In this article, the connection between the issue of depiction (taswir) and the concepts of “on” and “genesis” is discussed from the point of view of philosophy. In the same time, its connection to the concepts of creation and salvation are examined with regard to theology. Additionally, the author attempts at defining the theoretical foundation of representation and mimesis. Last but not least, the article aims at showing that the issue in question could be interpreted using the books of Ibn al-Arabi.
The Theoretical Foundations of Depiction (Taswir) with Regard to The Relation Between Representation and Mimesis –According to İbn Arabî’s Books
Keywords: Tasvir; Tasvir yasağı; Temsil; Taklit; Varlık; Oluş; Yaradılış; Kurtuluş; Felsefe; Sanat; Teoloji; Din; İslam; Tasavvuf; Depiction (taswir); Aniconism; Representation; Mimesis; Taklid; Existence; Creation; Salvation; Philosophy; Art; Theology; Religion; Islam; Tasawwuf